Immersive Science Learning: Flipbook Web-AR untuk Visualisasi dan Interaksi Konsep IPA - Fajariyanti, Nofita (Universitas Garut, 2025)
This research aims to evaluate the feasibility of Web Augmented Reality (Web-AR) based Digital Flipbooks as an innovative learning medium in supporting immersive learning in Natural Sciences (IPA) subjects. This medium is designed to present science material visually, interactively, and contextually, so that it can help students understand abstract concepts more concretely and interestingly. The evaluation process was conducted through validation by two media experts, using an assessment instrument that covered aspects of material completeness, image and video suitability, accessibility, design appeal, communication, and language. The validation results showed that this medium achieved an average score of 96.25, categorized as highly feasible. The experts assessed that the use of Web-AR technology in digital flipbooks enhances the appeal of learning, facilitates concept visualization, and supports active student engagement. In conclusion, the Web-AR Flipbook medium is deemed suitable for use in science education as part of an immersive learning approach. This medium has the potential to drive the transformation of conventional learning into a more interactive, flexible, and aligned approach with the Merdeka Curriculum, which emphasizes independent learning and real-world experiences. Keywords: Immersive learning, interactive digital books, web augmented reality, interactive media